(untitled) (Збірник наукових праць Галузеве машинобудування будівництво, 2022)
The current situation in the field of strength properties evaluation of sedimentary rocks using the express methods, such as penetration test, is analyzed. It is noted that a condition for setting up the relationship between the indicators of the physical state of sedimentary rock (natural moisture content, porosity coefficient) and indicators of mechanical properties (specific resistance to penetration, angle of internal friction, specific adhesion, deformation modulus) is the accumulation of test results to determine the listed characteristics of soils with a relatively constant plasticity number and genetically homogeneous. The results of parallel experimental studies of the physical and mechanical properties of sedimentary rocks of natural structure, including their penetration tests, are presented. The possibility of determining empirical equations of the relationship between physical (soil skeleton density and moisture content) and mechanical (specific resistance to penetration, angle of internal friction, specific adhesion, deformation modulus) characteristics of cohesive (light loams soils of loess origin) and non-cohesive (fine sands of quartz) sedimentary rocks of natural structure has been tested. The values of statistical indicators (coefficient of correlation, variation, and dispersion) of these equations substantiate a rather close relationship between mechanical and physical parameters. The possibility of studying the anisotropic properties of cohesive rocks of natural structure using penetration tests and determining empirical equations of the relationship between their physical and mechanical characteristics is also proved. A practical recommendation is given on the expediency of using correlation equations between the physical and mechanical properties of sedimentary rocks of natural structure to reduce the volume of laboratory tests in determining their mechanical parameters